Фінансова глобалізація: загрози і переваги для інвестиційної безпеки України - Коваль, Л. А.; Романчук, С. А.; Фабрика, І. В.; Koval, L.; Romanchuk, S.; Fabrika, І. (КНТУ, 2012)
В статті проаналізовано переваги і ризики фінансової глобалізації для ринку України і зроблено висновки, щодо можливих перспектив і загроз. The article analyzes the benefits and risks of financial globalization for the market of Ukraine and conclusions regarding the possible prospects and threats.
Financial globalization: challenges and benefits of the investment security of Ukraine
Keywords: ринок; фінанси; глобалізація; інвестиції; безпека; загрози; перспективи; переваги; ризик